Youth scaling up Climate Smart Agriculture in Zimbabwe - Kuipa, Prince (Technical Centre for Agricultural and Rural Cooperation, 2019)
Prince Kuipa, Chief Economist with the Zimbabwe Farmers Union (ZFU), a membership organisation representing mostly smallholder farmers, explains how they are involving young people in climate smart agriculture (CSA) approaches aimed at sustainably increasing productivity and incomes. CSA methods help farmers adapt to and become resilient to the impacts of climate change.